Exploring Reading Comprehension and Speed: A Study of SMAN 1 Mojo Students - Lestari, Nurul Dwi; Azizah, Syafrinnissa; Lailiyah, Siti; Yulaikha, Siti (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
The problem being analyzed during this research is dissimilarity in the effective reading ability between one student and others and the factors that affect the effective reading speed. The method used was a case study method combined with a quantitative methodology. Twenty-seven students were involved as the research subjects. The data were obtained from observation text entitled